THE EFFECT OF POLITICAL INSTABILITY IN COUNTRY PROSPERITY - Riak PhD, Gabriel Alier; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
Political instability simply the opposite of political stability; according to an early definition by Butkiewicz, James and Yanikkaya, (2010) a politically stable country had been a democracy or autocracy for at least 25 years (Cavallo and Cavallo, 2010). This definition would mean that political instability was just the non-persistency in form of government, no matter what type of rule (Bussière, Matthieu and Christian Mulder, 2008). Carmignani, (2009) related political instability to legitimacy of the political system, and thus a political system could only be more or less stable compared to it or other systems. This also suggests that individuals can be dissatisfied, loose confidence in the political system and act on their discontent (Gleditsch, Wallensteen, Sollenberg and Strand, 2012). The predominant view of political instability builds on both these definitions. Social unrest and civil disobedience may manifest itself through civil society, creating socio-political tension and a possible threat to political regimes.